ANALYSIS OF FACTORS INFLUENCING THE COLLABORATION OF COMMUNITY MENTAL HEALTH PROGRAM IMPLEMENTATION TEAMS IN JEMBER REGENCY - Heriberta Reny; Ika Barokah Suryaningsih; Suharsono (PT. Anagata Sembagi Education, 2025)
Interprofessional collaboration (IPC) is a strategy to address the need for integrated community mental health services. In community mental health services, effective interprofessional collaboration practices can increase community participation in carrying out early detection and prevention of mental health problems. In order to create effective IPC practices, it is necessary to identify factors that hinder interprofessional collaboration in community mental health programs. The purpose of this study was to analyze the level of Interprofessional Collaboration (IPC) of community mental health programs in Jember Regency. Methods: This study is a quantitative and qualitative research (mix-method). The level of interprofessional collaboration was measured using the PINCOM (The Perception of Interprofessional Collaboration Model) questionnaire consisting of 32 questions, which included individual factors and team factors. Questionnaire scores were calculated using a 5-point Likert scale. And further descriptive analysis using logistic regression. Then individual factors and team factors were further assessed using the in-depth interview method. The results of quantitative research show that the characteristics of respondents that affect the implementation of interprofessional collaboration are age, education, position, while employment status and length of service have no impact on the implementation of interprofessional collaboration in community mental health programs. The conclusion of this study is that the level of interprofessional collaboration in community mental health programs is running well, government policies are needed so that the handling of community mental health programs can be more comprehensive.